Analysis of Cost Acceleration Using Time Cost Trade Off Method on Wheat Silo and Pellet Silo Phase III Structure Repair Project in Surabaya - Klau, Maria Junita; Sajiyo, Sajiyo; Tjendari, Hanie Teki (CV. Proaksara Global Transeduka, 2024)
The Wheat Silo and Pellet Silo Structural Repair Project Phase III in Surabaya holds great significance in the wheat flour processing industry in Indonesia. PT Indofood Sukses Makmur Tbk Bogasari Surabaya Division, one of the leading wheat flour producers, required structural repairs on both silos to ensure smooth plant operations and final product quality. The project necessitates proper project management to avoid delays and cost overruns, with a budget of Rp. 28,011,000,000 and an estimated duration of 455 calendar days. This study employs the Time Cost Trade-Off (TCTO) method to analyze options for accelerating the project timeline by considering additional costs that may arise. The results showed that by using TCTO, the project completion time can be accelerated to 359 days from 455 days, reducing the duration by 21.10% at an additional cost of Rp. 739,351,125.00 or 2.64% of the project value. With the addition of 1 hour of overtime per day, the cost of accelerating the project is Rp. 413,445,000.00 or 1.48% of the project value, reducing the work time to 391 days or 14.07% of the original schedule.